(untitled) (Journal of Social Sciences Review, 2021)
It is an established fact that the teachers’ are the catalysts for improving the quality of teaching learning process. This focus is based on the assumption that understanding the perception of teachers’ on the contribution of principals’ instructional supervision towards the performance of teachers’. The principal is supposed to procure teaching materials to schools for teachers’ to work with in order to improve classroom instructions. Principals’ may always be ready to assist the teachers’ and interact with them in cordial manner. This study aimed to explore the “Relationship between Principals’ Instructional Supervision and Its Influence on Teachers’ Performance at Secondary Level in Peshawar” For this purpose data was collected, from 20 Girls high & higher secondary schools’ randomly. The population of the study comprised all the female teachers’ of Government Girls Secondary & Higher Secondary Schools .200 randomly selected female teachers’ made the sample of the study. To test the Reliability of the test items, a pilot study was carried out. The questionnaire was administered among 20 teachers’ other than the sample. Cronbach’s Alpha was carried out which yielded results within the acceptable range. Data was analyzed through SPSS applying various statistical tools including one sample t-test, the mean value of Interaction with Supervisor (IS) = 3.8714varies from mid-point (= 3) by .87140, and this variance is statistically significant at p < 0.01, and the mean value of Use of Instructional Material (UIM)= 3.3391 varies from mid-point (=3) by .33913 and this variance is statistically significant at p < 0.01. Coefficient Pearson Correlation of Interaction with Supervisor (IS) (M= 3.8714, SD= .67650) and AvM (M= 59.4250, SD= 10.80314), the coefficient of correlation of 0. 252* show that the two variables (IS) and AvM was significant. Coefficient Pearson Correlation of Instructional Material (IM) (M= 3.3391, SD= .70394) and AvM (M= 59.4250, SD= 10.80314), the coefficient of correlation of 0.157* shows that the two variables IS and AvM was significant. Regression analysis results shows that the whole research is statistically significant (F = 8.703; p = .000) and Independent variables is statistically significant (t = 2.950; p < 0.01).The Independent variables contributed statistically significantly in a positive way towards student achievement. Net Principals Instructional Supervision & Teachers Performance (NPISTP) is statistically significant (t = 2.950; p < 0.01). Dependent variable Student Achievement (SA) for unit = 7.211 increase in Independent variable IS & UIM. So, on the basis of the above results the Independent variable Interaction with Supervisor & Use of Instructional Material is positively contributes towards Student Achievement (SA) level. The main finding of the study included that teachers’ performance was positively correlated to the principals’ supervision. The study confirmed that the teachers’ participation and conferences and seminars provision of instructional material. The main conclusion of the study was that the principals’ effective supervision positively contribute towards teachers’ improved performance. The study do suggested that future researcher may take up the issue of instructional technology at secondary level.